HUBUNGAN PERSEPSI GURU TENTANG KOMPETENSI SUPERVISI KEPALA SEKOLAH DENGAN KINERJA GURU DI SMK DAAR AL MUHSININ KEC. NIBUNG ANGUS KAB. BATU BARA - Faruq Wijdan (Hijri, 2018)
As a supervisior of education, principals must be able to carry out various supervision and controls to improve the performance of education personnel in this case the teacher's performance. Supervision and control aims so that the teacher does not deviate in carrying out his work, of course the principal's supervision activities can be described directly in the form of teacher perceptions. The purpose of this understanding is to: 1) determine the level of tendency of teachers' perceptions of the competency of existing school principals; 2) knowing the level of teacher performance; and 3) a significant relationship between the supervisory competence of principals and the performance of existing teachers. The research subjects were teachers of the Daar Al Muhsinin Vocational School in Kec. Nibung Angus Kab. Coal with a population of 30 and a sample of 30. The overall sampling refers to the opinion of the arikunto suhars which states that if the population is less than 100, then the whole sample can be taken. Correlational research method that aims to explain the relationship between the two variables. The results of the study showed that the calculated average teacher perceptions of school principals' supervisory competence was 30%, and teacher's performance was 23%. Based on testing the hypothesis it can be concluded that the Teacher's Perception of Principal Supervision Competence (X) provides a weak relationship of 0.078 x 100% = 7.8% on Teacher Performance (Y) but can still be said to be significant. Furthermore, to determine the significance of the relationship between the two (teacher's perception of the principal's competence in teacher performance) can be seen through the ‘t test. Through the t test that has been done it turns out that t count = 1.540 while the value of t table = 1.701. Because t arithmetic (1,540) <t table (1,701), this shows that there is a weak and insignificant relationship between teacher perception variables regarding principals' supervisory competence and teacher performance with linear and predictive relationships through regression lines garis = 70,961 + 0.315 X, this regression line equation explains that if the teacher's perception of the supervisory competence of the principal increases by one unit, the Teacher's Performance will also increase by 0.315 + 70,961 = 71,276 units. Keywords: Principal Supervision, Teacher Performance